ZOSTERIFORM SKIN METASTASES: CLUE TO AN UNDIAGNOSED BREAST CANCER - Virmani, Neha C (Medknow Publications & Media Pvt Ltd, 2011)
Cancer metastases represent the most devastating aspect of malignancy, since the mortality of cancer patients is mainly related to the metastatic behavior of the primary neoplasm. Skin metastases are usually late events in the course of tumor progression. Excluding melanoma, the most common tumor to metastasize to the skin is breast cancer. Patients who develop cutaneous metastases rarely present with a zosteriform distribution. Herein, we present a 60-year-old female, an undiagnosed case of breast cancer, with zosteriform metastases along her right T2-T3 dermatome.